Differential inflammatory response of dental pulp explants and fibroblasts to saliva. (24th July 2015) - Cvikl, B.; Lussi, A.; Moritz, A.; Sawada, K.; Gruber, R.
Abstract: Aim: To investigate the inflammatory response of dental pulp fibroblasts and the respective explants to whole saliva. Methodology: Explants from human and porcine dental pulp tissue and isolated dental pulp fibroblasts were used to investigate the inflammatory response to sterile saliva. Cytokine and chemokine expression was assessed by RT‐PCR. Western blot analysis and pharmacologic inhibitors were used to determine the involvement of signalling pathways. Results: Dental pulp explants of human and porcine origin exposed to human saliva exhibited no major changes of IL‐6 and IL‐8 mRNA expression ( P > 0.05). In contrast, isolated porcine and human dental pulp fibroblasts, when stimulated with human saliva, exhibited a vastly increased expression of IL‐6 and IL‐8 mRNA ( P < 0.05). In pulp fibroblasts, saliva also increased the expression of other cytokines and chemokines via activation of NFkappaB, ERK and p38 signalling. Notably, a significantly reduced inflammatory response was elicited when pulp fibroblasts were transiently exposed to saliva. Conclusions: Saliva has a potential impact on inflammation of dental pulp fibroblasts in vitro but not when cells are embedded in the intrinsic extracellular matrix of the explant tissue.